2017
DOI: 10.1186/s12885-017-3566-0
|View full text |Cite
|
Sign up to set email alerts
|

Docetaxel, Cisplatin, and 5-fluorouracil (DCF) chemotherapy in the treatment of metastatic or unresectable locally recurrent anal squamous cell carcinoma: a phase II study of French interdisciplinary GERCOR and FFCD groups (Epitopes-HPV02 study)

Abstract: BackgroundThe squamous cell carcinoma of the anus (SCCA) is a rare disease, but its incidence is markedly increasing. About 15% of patients are diagnosed at metastatic stage, and more than 20% with a localized disease treated by chemoradiotherapy (CRT) will recur. In advanced SCCA, cisplatin and 5-fluorouracil (CF) combination is the standard option but complete response is a rare event and the prognosis remains poor with most disease progression occurring within the first 12 months.We have previously publishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 24 publications
(28 reference statements)
2
12
1
Order By: Relevance
“…In Epitopes-HPV02, 69 patients were enrolled between 17 September 2014 and 7 December 2016 and 66 patients were included for analysis (Figure 1). 13 We locked the database for Epitopes-HPV02 for updated analysis on 20 July 2020 with a median follow up of 40.1 months (95% CI 39.4-40.7). At data lock, 13 (19.7%) patients were still alive and free of progression.…”
Section: Resultsmentioning
confidence: 99%
“…In Epitopes-HPV02, 69 patients were enrolled between 17 September 2014 and 7 December 2016 and 66 patients were included for analysis (Figure 1). 13 We locked the database for Epitopes-HPV02 for updated analysis on 20 July 2020 with a median follow up of 40.1 months (95% CI 39.4-40.7). At data lock, 13 (19.7%) patients were still alive and free of progression.…”
Section: Resultsmentioning
confidence: 99%
“…Epitopes-HPV02 (NCT02402842) was a phase II multicenter prospective single-arm trial, in which the primary objective was to assess the efficacy of DCF regimen as first-line palliative chemotherapy for patients with SCCA. Detailed eligibility criteria and treatments have been reported elsewhere (16). Main eligibility criteria were: patients with unresectable locally advanced recurrent or metastatic SCCA; performance status: 0 or 1; no prior chemotherapy for metastatic or recurrent SCCA; signed informed consent.…”
Section: Patients and Samplesmentioning
confidence: 99%
“…We have previously shown promising results with the addition of docetaxel to DCF in our Epitopes-HPV01 cohort study [9]. Four patients (out of eight) presented a long-lasting remission, providing a clinical rational for a prospective multicentre phase II Epitopes-HPV02 trial of 66 SCCA evaluable patients [25]. The trial confirmed the efficacy of this combination and settled the mDCF regimen as a new standard first-line chemotherapy [5].…”
Section: Discussionmentioning
confidence: 72%